Another Division on Persian Comprehensive Preposition - ehsan esmaili (مطالعات زبانی و بلاغی)
Having a look at preposition in Persian grammar sources, we find out that these five comprehensive prepositions "to, with, on, from, in" have multiple grammatical behavior. It means they are sometimes an independent word and make complement clause and sometimes they are a part of another integrated whole and don’t make it. If the word is followed by is a complement clause, it would be whether a common complement or a proper complement. Proper complement is the same as object and is only used with transitive verb which must have object ,but common complement is not considered as object at all and is used with different kind of verbs like: transitive, intransitive, active , passive, linking or state and action verbs. If the preposition does not complement clause, it will be a dependent word or a part of a compound verb or a verb clause. It also can make compound adjective or adverbial and adjective clauses.